THE ROLE OF ISLAMIC EDUCATION IN PROMOTING GENDER EQUALITY: LESSONS FROM INNOVATIVE PROGRAMS AROUND THE WORLD - Hermansyah, Yus; Suhara, Djenal; Mukarom, Zaenal; Heriyanto, Imron; Al Bustom, Ali (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Islamic education has great potential in promoting gender equality through the teaching of the values of justice, equal rights, and respect for differences. This article explores the role of Islamic education in supporting gender equality by highlighting innovative programs around the world. From gender-responsive curricula in Islamic schools to community-based initiatives that promote women's participation in education and the economy, Islamic education can be a tool of social transformation. By taking lessons from programs in countries such as Indonesia, Egypt, and Western countries, this article shows that Islamic education can be a bridge to positive changes in gender relations, especially in the context of Muslim communities.